Urgensi Pendidikan Multikultural untuk Penguatan Karakter Sosial Peserta Didik pada Masyarakat Pesisir - Irwan Djumat; Irwan Abbas; Nani I. Rajaloa; Hasmawati Hasmawati; M. Arief Wicaksono (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2026)
The inculcation of multicultural values among the younger generation, particularly students at all levels of education, must continuously be carried out as an effort to protect them from exclusivist attitudes that may hinder the progress and civilization of humankind. One of the parties that plays an important role in disseminating multicultural values is educators and academics. Based on this concern, the lecturer team from the Civic and Pancasila Education Study Program, Faculty of Teacher Training and Education, Khairun University, conducted a Community Service Program in the form of a Focus Group Discussion (FGD) entitled “The Urgency of Multicultural Education for Strengthening Students’ Social Character in Coastal Communities” at SMA Tododara Maitara Tengah. The activity was implemented using lecture and discussion methods with the aim of equipping students with good character in facing the era of openness and information exchange. The stages of the activity included site observation, coordination with school authorities, implementation, and evaluation. The results showed that the inculcation of multicultural values at SMA Tododara Maitara Tengah was carried out through classroom learning activities across subjects as well as through positive habituation within the school environment. The implementation included encouraging students not to discriminate in choosing friends based on ethnicity, respecting religious holidays, practicing mutual cooperation during disasters or bereavement, cleaning places of worship, and maintaining environmental cleanliness. The recommendations of this activity are: (1) habituation and exemplary behavior should consistently be cultivated by students, teachers, and school leaders; and (2) multicultural education models should adapt to the development of information and technology as instruments that influence students’ character building.